Empowering Education with Augmented Reality: Planetarium Virtual Laboratory Development Society 5.0 Era - Nisa', Rofiatun; Isroil, Ahmad (UIN Sunan Kalijaga Yogyakarta, 2024)
Elementary school students in the Society 5.0 era have become accustomed to advanced technology. Therefore, teachers must make smart efforts to ensure the success of quality education. This research aims to analyze product practicality and product feasibility according to experts to support quality education for elementary school students in the Society 5.0 era. This study's Research and Development (RnD) method follows the ADDIE model. The research was conducted with sixth-grade elementary school students in Lamongan Regency, with 166 participants. Data analysis utilized interview and questionnaire techniques. The research results are as follows: The first stage involved analyzing the needs of teachers and students in IPAS learning that could support quality education relevant to the current era. The next stage was designing the learning media. After the design process, the learning media was developed and validated by two expert media validators, two science subject matter validators, and ten education practitioners in the very good category. The implementation results with sixth-grade students at Madrasah Ibtidaiyah in Lamongan showed that 90% of the students rated the media in the outstanding category. Thus, it can be concluded that this virtual planetarium laboratory media is effectively applied to sixth-grade students in science learning to support quality education in the Society 5.0 era.